2020
DOI: 10.1177/0033294119898117
|View full text |Cite
|
Sign up to set email alerts
|

Czech Version of the Spiritual Well-Being Scale: Evaluation and Psychometric Properties

Abstract: Spirituality and spiritual well-being are connected with many areas of human life. Thus, especially in secular countries, there is a need for reliable validated instruments for measuring spirituality. The Spiritual Well-Being Scale is among the world’s most often used tools; therefore, the aim of this study was its psychometrical evaluation in the secular environment of the Czech Republic on a nationally representative sample (n = 1797, mean age: 45.9 ± 17.67; 48.6% men). A non-parametric comparison of differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
3
3
0
Order By: Relevance
“…Our findings of differences in the level of spirituality among women and men are in line with previous research [ 24 , 27 , 57 , 58 , 59 ]. It is relatively common to talk about gender differences in psychology.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our findings of differences in the level of spirituality among women and men are in line with previous research [ 24 , 27 , 57 , 58 , 59 ]. It is relatively common to talk about gender differences in psychology.…”
Section: Discussionsupporting
confidence: 93%
“…Three models supported in previous studies [ 24 , 27 , 42 , 43 , 44 ] were examined in the current study: first, a one-factor model that includes all the items (Model 1); then a two-factor model with items separated into two factors, the Religious Well-Being (RWB) and Existential Well-Being (EWB) subscales (Model 2); and finally, a two-factor structure including only positive-worded items (Model 3). A second-order hierarchical model and a bifactor model could not be tested because in these models, the covariance matrices of latent variables were not positively definite and thus the standard errors could not be computed.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…However, previous validation studies [ 23 , 24 , 25 , 26 ], examining psychometric properties of various measures of Czech versions, revealed that NWIs are frequently associated with both decreased internal consistency of a scale and FL. It is therefore possible that in similar language environments (e.g., Slovak or Polish), NWIs may influence the psychometric quality of an instrument in a similar way.…”
Section: Introductionmentioning
confidence: 99%